Dynamic Decision-Making Model Analysis for Pandemic Spread Control Using Causal Loop Diagram - Bakti Nugraha, Arif (CoreID Journal, 2025)
Corona Virus Disease 2019 or better known as Covid 19 spreads very quickly and has become a pandemic for the world today. In its development process, it is very dynamic and complex, consisting of many interrelated and different components, each with its own purpose. As for the dynamic and complex issues in the spread of the Corona virus, the ability is absolutely necessary to limit the spread of the virus. For this reason, it is necessary to know the factors that influence and inhibit the spread of the virus as well as what strategies are needed and analyze the dynamic causality of these factors by using an approach method that uses a Causal Loop Diagram (CLD) system. The purpose of this study is to obtain an appropriate decision solution to manage the spread of the corona virus by using a causal graph approximation system.